Electrogenerated poly(pyrrole-lactosyl) and poly(pyrrole-3'-sialyllactosyl) interfaces: toward the impedimetric detection of lectins - Gondran, Chantal; Fort, Sebastien; Cosnier, Serge (Frontiers in Chemistry, 2013)
This paper reports on the impedimetric transduction of binding reaction between polymerized saccharides and target lectins. The controlled potential electro-oxidation of pyrrole-lactosyl and pyrrole-3’-sialyllactosyl at 0.95 V vs Ag/AgCl, provides thin and reproducible poly(pyrrole-saccharide) films. The affinity binding of two lectins: Arachis hypogaea, (PNA) and Maackia amurensis (MAA) onto poly(pyrrole-lactosyl) and poly(pyrrole-3’-sialyllactosyl) electrodes, was demonstrated by cyclic voltammetry in presence of ruthenium hexamine and hydroquinone. In addition, rotating disk experiments were carried out to determine the permeability of both polypyrrole films and its evolution after incubating with lectin target. Finally, the possibility of using the poly(pyrrole-lactosyl) or poly(pyrrole-3’-siallyllactosyl) films for the impedimetric transduction of the lectin binding reaction, was investigated with hydroquinone (2×10-3 mol L-1) as a redox probe in phosphate buffer. The resuting impedance spectra were interpreted and modeled as an equivalent circuit indicating that charge transfer resistance (Rct) and relaxation frequency (f°) parameters are sensitive to the lectin binding. Rct increases from 77 to 97 Ω cm2 for PNA binding and from 93 to 131 Ω cm2 for MAA binding. In parallel, f° decreases from 276 to 222 Hz for PNA binding and from 223 to 131 Hz for MAA binding. This evolution of both parameters reflects the steric hindrances generated by the immobilised lectins towards the permeation of the redox probe.